Development of a Modular Tool for Regulating and Analyzing Activities in Chess - Levon S. Berberyan (Изд-во НАН РА)
In this work computer software tool for regulating and analyzing activities in chess and approach to its design are suggested. The article starts with analyzing some common software for regulating and analyzing activities in chess, listing some of their pros and cons, especially concerning the chess engines comparison. Further, an improved software design approach to regulating and analyzing activities in chess based on separating software modules and defining API for each of them is specified
Keywords: Mathematics; Computer software